2009
DOI: 10.1186/1745-6215-10-76
|View full text |Cite
|
Sign up to set email alerts
|

Barriers encountered during enrollment in an internet-mediated randomized controlled trial

Abstract: Background: Online technology is a promising resource for conducting clinical research. While the internet may improve a study's reach, as well as the efficiency of data collection, it may also introduce a number of challenges for participants and investigators. The objective of this research was to determine the challenges that potential participants faced during the enrollment phase of a randomized controlled intervention trial of Stepping Up to Health, an internet-mediated walking program that utilized a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…This study had a higher rate of enrollment (58%) compared to many health targeted internet clinical trials previously reported [3539]. However, to reach these high enrollment completion rates, extensive effort was required for up to a year to enroll all participants who expressed interest but did not get through the consenting and baseline assessment process despite indicating interest and intent to do so.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This study had a higher rate of enrollment (58%) compared to many health targeted internet clinical trials previously reported [3539]. However, to reach these high enrollment completion rates, extensive effort was required for up to a year to enroll all participants who expressed interest but did not get through the consenting and baseline assessment process despite indicating interest and intent to do so.…”
Section: Discussionmentioning
confidence: 97%
“…Security for personal health information during assessments can be balanced with the provision of ready, unrestricted access to the internet site content. The INSPIRE project used similar techniques as other behavior change websites to engage participants and keep the website interesting and fresh, including tailoring, push emails, updated ‘News You Can Use’ and ‘Our Space’ comments’ [3541]. Our procedures for the development of the website were similar to those used by Mayer and colleagues [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mean age at enrolment of 61 years appears to be reasonably representative of the hypertensive population. Running a clinical trial online, where participants are entrusted to submit accurate data does raise data accuracy issues [20][21][22]. However, TIME does corroborate participant-reported data by record linkage of endpoints.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 11–34 At the patient level, demographic characteristics such as age, race, and gender have been commonly recognized as influential factors on patients’ participation. 4 , 19 , 21 , 23 , 33 , 35 , 36 Patients’ financial and socioeconomic status (SES), measured through factors such as insurance payer and education level, have also been shown to correlate with decision-making. 11 , 12 , 19 , 29 , 32 Besides these objective factors, the impact of patients’ subjective attitudes towards research is thought to be considerable – attitudes are also potentially influenced by family members and care providers, particularly in a pediatric setting.…”
Section: Introductionmentioning
confidence: 99%